SYNTAGMATICS OF HERO-AUTHOR CONNECTIONS IN THE WORKS OF LESYA UKRAINKA AND VASYL STEFANYK - Romanov, Sergiy (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
In the article, the work of Lesia Ukrainka and Vasyl Stefanyk is considered through the connections between the hero and the author. These connections in the study are taken as the basis for the development of the literary text due to the specifics of its functioning in the system writer – critic – reader. Thus, the aim of the work is to identify the features of the poetics of the main Ukrainian artists of the era of the frontier, in particular the defining in modernism plot and meaningful self-projection of creative personality. The results of scientific research in certain areas include: comparative delineation of the ways of work of writers with factual material (folklore, mythology, history, realities of the author's era, etc.); identifying the artistic style of the playwright and novelist; identification of leading ideological and plot models for both artists; analysis of the mechanisms of development and functioning of the character sphere; detection of algorithms of text influence on the reader. The achievements of practical significance in the proposed article can be considered to include the approbation of the individual search strategy in the science of Lesia Ukrainka and Stefanyk studies, implemented in the fields of literary, philosophical and psychological discourses. Under this review, the frontal application of the methods of comparative studies for the study of artistic phenomena of the mononational register may also be interesting. In terms of scientific novelty, the article also differs primarily in the way of researching psychobiographies and creative paths of contemporary writers, which is to compare the identities of artists associated with the phenomenon, trend and personal relationships.